Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Pada Pt Permodalan Nasional Madani Kelompok Cianjur SP1 Kab. Sorong - Anisa Nurbadriah; Karfin (At-Thariqah: Jurnal Ekonomi, 2025)
This study aims to determine the influence of service quality on customer satisfaction on loans at PNM Mekaar. This study uses a quantitative approach method. The sample of this study is 41 respondents from all customers in SP1. Data was collected through questionnaires that were shared directly and analyzed using simple linearity to test the hypothesis proposed. The results of the study show that there is a significant influence between service quality and customer satisfaction. This shows that the better the quality of service provided, the higher the level of customer satisfaction. The conclusion of this study is that the quality of the service provided has a positive impact on customer satisfaction. Therefore, it is recommended for employees to always maintain and improve the quality of service. This research is expected to be a reference material for the company in maintaining and improving the quality of services provided.